Notions of personhood, the political and relationalities: Paradigms of the anthropology of nature - Geviller Marín; Francisco Neira; María Elena Ramírez; Diana Soto; Javier Vásconez; Ivette Vallejo (Íconos)
The article offers a conceptual journey of anthropology focusing on the way in which the relationship between societies and the environment has been framed, facing a turning point with the so-called "anthropology of nature". In this work, foundational concepts such as adaptation, nature, culture, otherness and personhood are rethought. The aim of the article is to address the paradigmatic break that has allowed anthropology to connect and engage in dialogues with other disciplines, such as ecology, sociolinguistics and philosophy, paying attention to the complexity and suggesting the uniqueness between nature and culture, in opposition to the dichotomous and fragmentary approaches that separate them. The article is the product of the revision and contrast of theories and approaches between the mentioned disciplinary fields. The article also presents some approximations about the theoretical and the empirical, with examples taken from the literature of the Andes and Amazon. In the conclusions the article highlights the relevance that the emphasis on the anthropology of nature has had by focusing on the subjectivity and agency of non-human beings, and in reframing the philosophical category of person from multinaturalism, causing an ontological twist. This has allowed for the enrichment of the debate about what is considered a subject agent in the world and therefore subject of law, with ethical approaches to deal with the problems of the anthropocene.